Therapeutic Applications of Human and Bovine Colostrum in the Treatment of Gastrointestinal Diseases and Distinctive Cancer Types: The Current Evidence - Bagwe-Parab, Siddhi; Yadav, Pratik; Kaur, Ginpreet; Tuli, Hardeep Singh; Buttar, Harpal Singh (Frontiers in Pharmacology, 2020)
The incidence of gastrointestinal disorders (GID) and cancers is escalating all over the world. Limited consumption of colostrum by the new born not only weakens immune system but also predisposes the infant to microbial infections. Colostrum is the nature’s perfect food and ‘elixir of life’. Breast-fed infants have a lower incidence of GI tract infections than infant-fed formula or cow’s milk. As per WHO statistics, cancer is the most prevalent disease globally and causes 9.6 million deaths worldwide. The current strategies for treating cancer include chemotherapy, radiation, and surgery. However, chemotherapy and radiation exposure is usually associated with serious long-term side effects and deterioration in the quality of life (QOL) of patients. Furthermore, the hospitalisation and medication costs for treating cancers are exorbitant and impose high economic burden on the health care systems. People are desperately looking for cost-effective and affordable alternative therapies for treating GID and cancers. Therefore, there is an urgent need for clinically evaluating the anticancer compounds isolated from plants and animals. Such therapies would not only be economical and have lesser side effects, but also help to improve the QOL of cancer patients. Recently, bovine colostrum (BC) has caught the attention of many investigators to explore its anticancer potential in humans. BC impregnated dressings are highly effective in treating chronic wounds and diabetic foot ulcer. BC is rich in lactoferrin, a glycoprotein with strong anti-oxidant, anti-inflammatory, anti-cancer, and anti-microbial properties. Intravaginal application of BC tablets is effective in causing regression of low-grade cervical intraepithelial neoplasia. The underlying mechanisms of BC at cellular, genetic, and molecular level remain to be ascertained. Oral BC supplement is well tolerated, but some people may experience problems such as flatulence and nausea. Well-designed, randomized, placebo-controlled, clinical trials are needed to access the therapeutic potential, long-term safety, and optimal doses of BC products. This review is aimed to highlight the anticancer potential of BC and its components, and the therapeutic applications of BC supplements in treating gastrointestinal diseases in children and adults. We also discuss the health promotion benefits and therapeutic potential of BC nutraceuticals in reducing the incidence of non-communicable diseases.